Integrated social work management model in the Republic of Slovenia - Colnar, Simon (Socialno delo, 2018)
The social work of today is dealing with partially unsuitable knowledge, which has been produced in a different epoch of the welfare state and as a consequence, social work is still dominated by various twentieth century theories that are primarily focused on direct practice expertise. Nowadays social work globally has changed and in order to achieve desirable outcomes, social workers also need to understand and learn about complementary skills that extend their extensive knowledge about direct practice. Already back in 2004, management was recognised as one of the 13 core purposes of the social work profession, however, there are still concerns about social workers' lack of knowledge and skills in management practice. Authors believe that management can help in the progress of the field. Based on a thorough literature review and analysis of existing secondary data, authors propose a systematic approach towards an improved social work management model that integrates the field of social work with related areas (namely humanitarian organisations, the deinstitutionalisation process, calls for higher process and budget efficiency, appropriate management skills and organisational design). These five pillars of the integrated social work management model, therefore, advance the frontiers of social work science. The authors also discuss the contribution of the model to the social work management theory and its practical usefulness.
Keywords: deinstitucionalizacija; humanitarne organizacije; javna uprava; management; Slovenija; socialna varnost; socialne storitve; socialno delo